The Impact of PSAK 71 Implementation On Bank Profitability In Indonesia - Mulyanengsih, Ratna (Gema Wiralodra, 2024)
This study investigates the impact of PSAK 71 implementation on the profitability of banks in Indonesia, measured through financial performance indicators such as Return on Assets (ROA) and Return on Equity (ROE). It also examines the effects of liquidity risk, credit risk, capital adequacy, bank size, loan growth, and non-interest expenses on bank performance. Using panel data from Indonesian banks spanning several years, the study employs a quantitative approach and applies the Fixed Effects Model, selected through Chow, Hausman, and Lagrange Multiplier tests, to analyze the relationship between these variables. The findings reveal that PSAK 71 has significantly influenced credit provisioning practices, necessitating proactive risk management strategies. Liquidity risk, measured by the Loan-to-Deposit Ratio (LDR), and credit risk, represented by Non-Performing Loans (NPL), are identified as critical factors negatively affecting profitability. Capital adequacy ratios (CAR) positively influence ROA but have mixed effects on ROE. While loan growth contributes positively to bank performance, larger bank sizes and higher non-interest expenses tend to exert downward pressure on profitability. These results highlight the interplay between regulatory changes and financial performance, emphasizing the importance of risk management and capital optimization in navigating a rapidly evolving banking environment. This research offers practical insights for policymakers, banking professionals, and stakeholders, supporting the development of strategic frameworks to enhance resilience and sustain profitability in the Indonesian banking sector under PSAK 71 regulations.